Sinners [videorecording (Blu-Ray)] - Coogler, Ryan, 1986-; Jordan, Michael B. (Michael Bakari), 1987-; Steinfeld, Hailee; Caton, Miles; O'Connell, Jack, 1990-; Mosaku, Wunmi; Lawson, Jayme, 1997-; Miller, Omar Benson; Guy, Buddy; Lindo, Delroy, 1952-; Durald Arkapaw, Autumn, 1979-; Göransson, Ludwig, 1984-; et al. (Warner Bros. Entertainment Inc., 2025)
Trying to leave their troubled lives behind, twin brothers return to their hometown to start again, only to discover that an even greater evil is waiting to welcome them back.